Relationship complexities among women with obstetric fistula in Zimbabwe: an exploratory study - Maunganidze, Levison; Sodi, Tholene; Mutambara, Julia; Nkiwane, Sibusiso (Routledge, 2016)
This study sought to determine how obstetric fistula affects women's intimate partner relationships or other social ties. A purposive sampling of eleven women (age range 17 to 31) with obstetric fistula admitted to two hospitals in Zimbabwe was done. In-depth interviews using unstructured interview guides were used to collect data on how the women`s condition impacted the way they related to other people and vice versa. Data were grouped into themes and analysed using content analysis and languishing and flourishing experiences were reported by the participants. Most of the study participants indicated that the condition strained their relationship with their husbands since they could not fulfil their conjugal rights. Participants also reported stigma from their close associates in the community, including extended family. Other participants reported to experience spiritual growth and strength from living with obstetric fistula. Support networks are important for women with obstetric fistula in a in a low resourced country like Zimbabwe.